Structural performance of concrete-filled square steel tubular columns encased with I-shaped CFRP under eccentric compression. (1st December 2021) - Li, Guochang; Sun, Xing; Yang, Zhijian; Fang, Chen; Chen, Bowen; Ge, Hanbin; Liu, Yaopeng
Highlights: Conducted eccentric compression tests on 18 CFSST-CFRP long column. Investigated eccentrically loaded behavior and resistance of CFSST-CFRP column. Evaluated effects of slenderness ratios and load eccentricity ratio. Analyzed load bearing capacity and load-transferring mechanism. Performed parametric studies on column bearing capacity. Developed design equations to predict ultimate eccentric load capacity. Abstract: This study investigated behavior of concrete filled square steel tubular (CFSST) columns encased with I-shaped CFPR under eccentric compression. Full-scale eccentric compression tests were conducted on eighteen column specimens consisting of square steel tube, concrete, and an I-shaped CFRP profile. The test program considered effects of load eccentricity ratio and column slenderness ratio. The eccentrically loaded column behavior was investigated with respect to the mid-height deflection, load, and failure modes. The development and distribution of longitudinal strain and neural axis for the column were also studied. Finite element models were developed and validated against tested results to further analyze the load-transferring mechanism of the composite column and perform detailed parametric studies. The results indicated that the CFSST column encased with I-shaped CFRP behaved in a ductile manner with the improved capacity and increased stability. Finally, design equations were developed using tested and simulated data to estimate ultimate bearing capacity of the CFSST column encased with I-shaped CFRP when subjected to eccentric compression. The predicted column capacities using the design equations matched well with the tested and simulated capacities.